Antiretroviral pill count and clinical outcomes in treatment‐naïve patients with HIV infection. Issue 2 (6th November 2017) - Young, J; Smith, C; Teira, R; Reiss, P; Jarrín Vera, I; Crane, H; Miro, JM; D'Arminio Monforte, A; Saag, M; Zangerle, R; Bucher, HC; ,
Abstract : Objectives: Treatment guidelines recommend single‐tablet regimens for patients with HIV infection starting antiretroviral therapy. These regimens might be as effective and cost less if taken as separate drugs. We assessed whether the one pill once a day combination of efavirenz, emtricitabine and tenofovir reduces the risk of disease progression compared with multiple‐pill formulations of the same regimen. Methods: We selected treatment‐naïve patients starting one‐, two‐ or three‐pill formulations of this regimen in data from the Antiretroviral Therapy Cohort Collaboration. These patients were followed until an AIDS event or death or until they modified their regimen. We analysed these data using Cox regression models, then used our models to predict the potential consequences of exposing a future population to either a one‐pill regimen or a three‐pill regimen. Results: Among 11 739 treatment‐naïve patients starting the regimen, there were 386 AIDS events and 87 deaths. Follow‐up often ended when patients switched to the same regimen with fewer pills. After the first month, two pills rather than one was associated with an increase in the risk of AIDS or death [hazard ratio (HR) 1.39; 95% confidence interval (CI) 1.01‐1.91], but three pills rather than two did not appreciably add to that increase (HR 1.19; 95% CI 0.84‐1.68). We estimate that 77 patients would need to be exposed to a one‐pill regimen rather than a three‐pill regimen for 1 year to avoid one additional AIDS event or death. Conclusions: This particular single‐tablet regimen is associated with a modest decrease in the risk of AIDS or death relative to multiple‐pill formulations.